Fertility Tourism: The legal side of this phenomenon without borders - Barbu, Raluca Maria (Bioethica, 2022)
Fertility, reproductive or procreative tourism are all new terms which designate a growing trend of the 21st century, namely the movement of people to other countries in order to undergo fertility treatment. Thus, this phenomenon implies multiple legal, bioethical, sociological issues and more, which need to be taken into consideration both by the national policymakers and by the ones seeking for such treatments abroad. This review article will try to offer a bigger picture by focusing on the particularities of the national laws on medical assisted reproduction of four representative EU countries, namely Germany, Austria, Italy and France and on interpreting how the restrictions in one state could boost the fertility tourism industry in other ones. The situation in each country will be depicted in a comparative manner, tackling the legislation, regulations and even relevant domestic jurisprudence on topics such as gamete donation and its anonymity regime, post-mortem reproduction, surrogacy services and cryopreservation. Moreover, it will be determined who is entitled to have fertility treatment in each of the countries subject of the analysis and how do these states fund the procedures. Furthermore, the most popular non-EU countries of destination will be presented and why one would prefer to undergo fertility treatment there. In the end, the review article will reflect if there are indeed real chances of creating strong national, European or international policies regarding fertility treatments.